Politik Perempuan dalam Pemilihan Umum Tahun 2024 dan Tantangan Menuju Kesetaraan Gender - Anang Dony Irawan; Devi Mutiara Sanni; Desi Farika Ambarwati; Arin Vevi Ayu Putri Hermawan (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research aims to analyze women's political rights and position in the 2024 General Election and identify the challenges faced in achieving gender equality. Women's rights and political position are the main focus, with an emphasis on their participation and representation in the political process in the 2024 General Election. The issue of women's representation is very important because many policies are considered not pro-women, such as the Draft Law on the Elimination of Sexual Violence and many more. Even though the quota has not yet been reached, this year the representation of women has increased. There needs to be special attention to the issue of women's representation in politics. The method used in this research is normative legal research with a statutory regulation approach. Data was collected from primary and secondary sources related to the political position of women in the 2024 General Election and the challenges towards gender equality. This is important to analyze in depth as a representation that women and men are equal, so that they have the same rights in the implementation process of the General Election. Continuous commitment is needed from all levels of society to achieve this goal. This conclusion emphasizes that to achieve gender equality in politics, integrated efforts are needed from various parties, including the Government, civil society, educational institutions and the media. Only with strong cooperation can we hope to create a more inclusive and equal political environment for women.